Thromboprophylaxis and death after total hip replacement. - Murray, D; Britton, A; Bulstrode, C (1996)
The recommendation that patients having a total hip replacement should receive pharmacological thromboprophylaxis is based on the belief that fatal pulmonary embolism is common, and that prophylaxis will decrease the death rate. To investigate these assumptions we performed a meta-analysis of all studies on hip replacement which included information about death or fatal pulmonary embolism. A total of 130 000 patients was included. The studies were so varied in content and quality that the results of our analysis must be interpreted with some caution. The fatal pulmonary embolism rate was 0.1% to 0.2% even in patients who received no prophylaxis. This is an order of magnitude lower than that which is generally quoted, and therefore the potential benefit of prophylaxis is small and may not justify the risks. To balance the risks and benefits we must consider the overall death rate. This was 0.3% to 0.4%, and neither heparin nor any other prophylactic agent caused a significant decrease. Our study demonstrates that there is not enough evidence in the literature to conclude that any form of pharmacological thromboprophylaxis decreases the death rate after total hip replacement. For this reason guidelines which recommend their routine use to prevent death after hip replacement are not justified.